THE IMPACT OF MACROECONOMIC INDICATORS ON ECONOMIC GROWTH IN INDONESIA, MALAYSIA AND SINGAPORE - Imleesh, Rabeea Mohammed; Yanto, Heri; Prajanti, Sucihatiningsih Dian Wisika (Journal of Economic Education, 2017)
Economic growth refers to the development of a country's economic activity is causing the goods and services produced within the community to grow and increase the prosperity of the community in the long term. The economic growth is one of the indicators used to assess the success of development. In the actual economic activity, economic growth showed the physical economic development taking place in a country, such as increasing the number and production of industrial goods, development of infrastructure, increase the number of public facilities such as schools, hospitals, roads, development of manufacturing goods, and so on. In principle, not all of the negative impact of inflation on the economy. Especially in case of mild inflation are inflation below ten percent. The inflation rate is the annual percentage increase in the general price level as measured by the consumer price index. The relationship between economic growth and macroeconomic indicators has long been a popular issue of debate in the literature of economic development. In this content, the primary purpose of this research is to analyze macroeconomic indicators of Indonesia and economic growth using panel data approach. To compare with another countries in developing countries so will use Malaysia and Singapore. Also in this research will analyze the relationship between inflation and interest rate with economic growth because inflation and interest rate closely related to macro economy and economic growth in a country.